DAMAGE TO THE ARTERIES OF THE LOWER LIMB DUE TO BONE FRACTURES: A CASE REPORT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
A 38-year-old male patient, A.H., sustained multiple injuries, including a femoral fracture with damage to the superficial femoral artery (SFA) and fractures of the right 1st to 8th ribs, after falling from a height of four meters during a handstand. The patient underwent simultaneous surgical interventions, including crossectomy of the great saphenous vein, autovenous grafting of the SFA to restore vascularization, and retrograde intramedullary locked nailing of the femur. After four weeks, the patient was discharged from the hospital, bearing weight on both lower limbs with the assistance of a walker.